Audit Manajemen Sumber Daya Manusia Untuk Menilai Efektivitas Dan Efisiensi Terhadap Fungsi Rekruitmen, Pelatihan Dan Pengembangan Karier, Dan Penilaian Kinerja Sumber Daya Manusia Pada PT. Limpah Mas Indonesia (LMI) Cabang Surabaya - Anastasya Mechta Mediana; Hwihanus Hwihanus (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research aims to assess the effectiveness and efficiency of the recruitment, training and career development functions, as well as assessing the performance of PT's human resources (HR). Limpah Mas Indonesia (LMI) Surabaya Branch. This research uses a qualitative descriptive research method with data collection techniques in the form of observation, interviews and questionnaires. The research results show that the functions of recruitment, training and career development, as well as employee performance assessment at PT. Limpah Mas Indonesia (LMI) Surabaya Branch has been running effectively and efficiently. Based on the audit findings, several recommendations for PT. Limpah Mas Indonesia (LMI) Surabaya Branch as input material that can be used in improving recruitment, training and development functions, as well as performance appraisals, among which companies must document work agreements, company regulations and policies in writing to provide legal certainty for employees and the company, evaluation employee training and career development programs are carried out regularly, companies should add more diverse performance assessment methods to provide a more comprehensive picture of employee performance.